2021
DOI: 10.7759/cureus.18765
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Pregnancy Screening for Group B Streptococcus Infection Among Women of Reproductive Age and Physicians in Jeddah, Saudi Arabia

Abstract: BackgroundGroup B Streptococcus is part of the normal flora of the female urogenital tract and rectum. Vaginal colonization and transmission of this bacteria during delivery can lead to neonatal life-threatening complications, which can be prevented by screening and the administration of intrapartum antibiotics. This study's aim was to assess the level of awareness of antenatal screening of Group B Streptococcus among women and physicians in Jeddah, Saudi Arabia. MethodsA cross-sectional study using an online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…11 Invasive infections cause more than 1.4 million neonatal deaths each year, and in Saudi Arabia, the rate ranges from 9.2% to 31.6%, depending on the region. 7,10,12 The Centers for Disease Control and Prevention (CDC) recommends regular screening of pregnant women between 35 and 37 weeks to detect colonized mothers and treat those infected with antibiotics. 7,13 For GBS pregnancy screening, universal culture-based and risk-based screening are viable options.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Invasive infections cause more than 1.4 million neonatal deaths each year, and in Saudi Arabia, the rate ranges from 9.2% to 31.6%, depending on the region. 7,10,12 The Centers for Disease Control and Prevention (CDC) recommends regular screening of pregnant women between 35 and 37 weeks to detect colonized mothers and treat those infected with antibiotics. 7,13 For GBS pregnancy screening, universal culture-based and risk-based screening are viable options.…”
Section: Introductionmentioning
confidence: 99%
“…7,10,12 The Centers for Disease Control and Prevention (CDC) recommends regular screening of pregnant women between 35 and 37 weeks to detect colonized mothers and treat those infected with antibiotics. 7,13 For GBS pregnancy screening, universal culture-based and risk-based screening are viable options. 3 Reducing the occurrence of early-onset neonatal sepsis and preventing death are related to a universal culture-based screening program and early delivery of intrapartum antibiotics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, there is no unified national CPG in Saudi Arabia for the management of sepsis ( 15 ). Furthermore, GBS screening for pregnant women is not a standard of care in Saudi Arabia yet ( 16 ). A recent cohort study identified the risk for early NS in Saudi Arabia to be 0.5/1,000 live births ( 17 ).…”
Section: Introductionmentioning
confidence: 99%